2016
DOI: 10.1177/0149206315621145
|View full text |Cite
|
Sign up to set email alerts
|

Board Interlocks and Initial Public Offering Performance in the United States and the United Kingdom: An Institutional Perspective

Abstract: Sun Yat-sen UniversityBuilding on the institutional perspective on capital markets, we examine the process of legitimation that underpins investor valuation of initial public offerings in the context of institutional polycentricism. We focus on the impact of board interlocks of the CEO and internal and external board members on investor perceptions of initial public offering firms in the United States and United Kingdom. We find that the extent of board members' interlocks relates positively to the extent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 75 publications
(166 reference statements)
2
34
0
1
Order By: Relevance
“…Recent studies showed that board size impacts financial variables as market value, risk, and ROA [38,54]. Also, it is a relevant characteristic of the board's structure [23,55].…”
Section: Board Sizementioning
confidence: 99%
“…Recent studies showed that board size impacts financial variables as market value, risk, and ROA [38,54]. Also, it is a relevant characteristic of the board's structure [23,55].…”
Section: Board Sizementioning
confidence: 99%
“…a last resort) driven by a lack of external financing, entrepreneurs also proactively use bootstrapping techniques (Grichnik, Brinckmann, Singh and Manigart, 2014;Winborg, 2009). Some 95% of firms in the studies by Freear, Sohl and Wetzel (1995) and Harrison, Mason and Girling (2004) were engaged in at least some bootstrapping activities. Despite its prevalence, research on financial bootstrapping remains scarce-even when we consider studies that have focused on some individual bootstrapping techniques, such as leasing and using subsidy financing (e.g.…”
Section: Challenging Common Wisdom With Respect To "Traditional" Sourmentioning
confidence: 99%
“…Considering the importance of entrepreneurial firms for the overall economic system, there is a need for research on these distinct sources of financing, to understand how they impact startups (Fraser, Bhaumik and Wright, 2015) and how these new (or generally ignored) phenomena shape existing theories. Previous studies emphasized the peculiarity of the entrepreneurial settings to study mainstream theories such as agency theory (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sociological and institutional perspectives on financial market behavior suggests an alternative theoretical approach to the role of macro-institutions by arguing that capital market reactions to firm-level financing strategies are institutionally embedded (Bell, et al, 2014;Zajac and Westphal, 2004). From this perspective, market perceptions of the firm's actions are an outcome of investors' perceptions of its legitimacy rather than rational, efficiency-centered investor decisions (Filatotchev, Chahine and Bruton, 2016). Legitimacy is the "generalized perception or assumption that the actions of an entity are desirable, proper, or appropriate, within some socially constructed system of norms, values, beliefs, and definitions" (Suchman, 1995: 574).…”
Section: Implications Of Differences Between Product and Capital Markmentioning
confidence: 99%
“…These arguments provide novel dimensions to the institutional perspective in IB research by suggesting that capital market strategies may be framed not only by underlying efficiency models but also by differences in cultural, macro-institutional factors that underpin institutional logics in different capital markets (Filatotchev et al, 2016) as indicated in Table 2. Grinblatt and Keloharju (2000) found that investors are more likely to hold, buy, and sell the stocks of firms that are located close to the investor, that communicate in the investor's native tongue, and have chief executives of the same cultural background.…”
Section: Culture and Capital Marketsmentioning
confidence: 99%